Relative Importance of Four Muscle Groups for Indoor Rock Climbing Performance. Issue 7 (July 2015) - Deyhle, Michael R.; Hsu, Hung-Sheng; Fairfield, Timothy J.; Cadez-Schmidt, Taryn L.; Gurney, Burke A.; Mermier, Christine M.
Abstract : Abstract: Deyhle, MR, Hsu, H-S, Fairfield, TJ, Cadez-Schmidt, TL, Gurney, BA, and Mermier, CM. Relative importance of four muscle groups for indoor rock climbing performance. J Strength Cond Res 29(7): 2006–2014, 2015—Little research is available to guide training programs for rock climbers. To help meet this need, we sought to determine the relative importance of 4 muscle groups for rock climbing performance. Eleven male climbers were familiarized with an indoor climbing route before 5 separate days of testing. On testing days, subjects were randomly assigned to climb with no prefatiguing exercise (control climb) or after a prefatiguing exercise designed to specifically target the digit flexors (DF), shoulder adductors (SA), elbow flexors (EF), or lumbar flexors (LF). Immediately after the prefatiguing exercise, the subject climbed the route as far as possible without rest until failure. The number of climbing moves was recorded for each climb. Surface electromyography of the target muscles was recorded during the prefatigue. Fewer climbing moves were completed after prefatigue of the DF (50 ± 18%) and EF (78 ± 22%) ( p ⩽ 0.05) compared with the control climb. The number of moves completed after prefatigue of the LF and SA were not statistically significant compared with the control climb ( p > 0.05). The short time lapse between the end of prefatiguing exercise and the start of climbing (transit time), which may have allowed for some recovery, was not different among trials ( p > 0.05). Electromyography median frequency was reduced from beginning to end of each prefatiguing exercise. These results suggest that among the muscle groups studied in men, muscular endurance of DF and EF muscle groups is especially important for rock climbing on 40° overhanging terrain.